A non-linear business process management maturity framework to apprehend future challenges. (December 2019) - Froger, Manon; Bénaben, Frederick; Truptil, Sébastien; Boissel-Dallier, Nicolas
Highlights: Business Process Management (BPM) Maturity levels are not necessarily linear. BPM Maturity can be assessed along 3 axes: Fields, Abstraction Level and BPM cycle. Information Technology constitutes a critical Field just as much as Business and Culture. Achievements resulting from the intersection of the 3 axes are not all independent. Interactions between achievement raises the possibility of an optimum BPM strategy. Abstract: In a context where enterprises and organizations aim to optimise their behaviour, obtain certifications and labels, and benefit from the smart use of information systems and technology, two considerations drive this research: (1) the weak maturity level of worldwide Business Process Management (BPM), which exposes the need to reconcile academic theories with industrial contexts, and (2) the need for upcoming software functionalities that prioritize removing the barriers frequently encountered by industrialists when trying to implement the method. To reach such goals, this research work has developed a conceptual framework to represent the BPM implementation state. It is built along three axes: the BPM Cycle (Design, Enact, Maintain), the Field (Culture, Business, IT) and the Abstraction Level (Data, Jobs, Behaviour). An organization's overall BPM maturity can thus be evaluated by positioning its capabilities along the framework's axes. It is also suggested that the framework be used to track the implementation of new procedures in an organisation. The framework is presented and detailed before being applied to a complete case study.